Development of composting process of oil palm industrial wastes by multi-enzymatic fungal system - Mohammad, Noor; Alam, Md Zahangir; Kabashi, Nassereldin (Springer Japan, 2013)
There is an increased interest in composting as an effective means of handling large amounts of organic wastes generated by oil palm industries in Malaysia. However, very few studies have been conducted to develop an effective composting process using the multi-enzymatic system. This study demonstrates an effective composting process of EFB (empty fruit bunch) with POME (palm oil mill efﬂuent), using the optimized process parameters and compatible multi-enzymatic fungal system. A higher decrease (3 %) of organic matter was achieved in the fungal treated system, almost double that of the control (without inoculum). The lowest C/N ratio and soluble protein content recorded were about 17 and 128.82 g/kg, respectively. The maximum germination index obtained was 116 % at day 50 of treatment, which is considered high compared to the control (uninoculated). Furthermore, the maximum activity of ligninase enzyme was found to be 25.95 U/g and the highest cellulase activity was recorded at 0.975 U/g.